STUDENT’S ABILITY IN READING COMPREHENSION - Fajar Aldiansyah; Nuranisa Hasibuan; Sulistina Ratulani Simbolon; Emeliya Sukma Dara (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
This research targets to enhance pupil’s capability in reading comprehension so that the scholars are able to apprehend studying texts from books or other analyzing media. The pattern of this studies became students of eighth (2) Grade MTs Laboratorium Uinsu. This studies uses a qualitative and quantitative strategies. The research used observations and questionnaires because the device. The consequences of this look at suggest that the capability of the 8th (8) grade students of MTs Laboratorium Uinsu is pretty awful, they are very hard to recognize antonyms and synonyms of a word due to the lack of vocabulary they have got.